Treatment of severe pneumonia due to COVID-19 with peginterferon alfa 2a. (2020) - El-Lababidi, Rania M.; Mooty, Mohamad; Bonilla, Maria-Fernanda; Salem, Nouran M.
Highlights: To date, there is no definite treatment identified for COVID-19. Interferon therapy has been used in the treatment of SARS and MERS. In this case series we report on the use of peginterferon alfa 2a in the treatment of severe pneumonia due to SARS-CoV-2. Abstract: The outbreak of the new coronavirus disease 2019 (COVID-19) has spread rapidly worldwide. Until now, no definite effective treatment has been identified. We reported 3 patients with severe COVID-19 treated with pegylated interferon alfa 2a with satisfactory recovery. Based on these observations, randomized studies with interferons should be considered in deteriorating patients infected with COVID-19.